SensoTrust: Trustworthy Domains in Wireless Sensor Networks. (1st July 2015) - Castillejo, Pedro; Martínez-Ortega, José-Fernán; López, Lourdes; Sánchez Alcón, José Antonio
Abstract : Wireless sensor networks (WSNs) based on wearable devices are being used in a growing variety of applications, many of them with strict privacy requirements: medical, surveillance, e-Health, and so forth. Since private data is being shared (physiological measures, medical records, etc.), implementing security mechanisms in these networks has become a major challenge. The objective of deploying a trustworthy domain is achieving a nonspecific security mechanism that can be used in a plethora of network topologies and with heterogeneous application requirements. Another very important challenge is resilience. In fact, if a stand-alone and self-configuring WSN is required, an autosetup mechanism is necessary in order to maintain an acceptable level of service in the face of security issues or faulty hardware. This paper presents SensoTrust, a novel security model for WSN based on the definition of trustworthy domains, which is adaptable to a wide range of applications and scenarios where services are published as a way to distribute the acquired data. Security domains can be deployed as an add-on service to merge with any service already deployed, obtaining a new secured service.